Integrating refugees into the Turkish labour market - Del Carpio, X; Seker, S; Yener, A (Refugee Studies Centre, University of Oxford, 2018)
The granting to Syrian refugees in Turkey of the right to access formal work was a first step towards their economic integration but a number of challenges remain. With support from the international community, the Turkish government is taking action to overcome some of these.